1957
DOI: 10.1111/j.1744-7348.1957.tb00411.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND NUTRITION OF TIMOTHY (PHLEUM PRATENSE L.) III. ABSORPTION AND DISTRIBUTION OF NITROGEN, PHOSPHORUS AND POTASSIUM DURING THE FIRST YEAR OF GROWTH

Abstract: Absorption of nitrogen, phosphorus and potassium by S48 timothy plants ran parallel to dry‐weight increase, at an increasing rate until the autumn, almost completely ceasing in the winter, and increasing again in the spring. Flowering tillers accumulated nutrients until ear emergence, after which the content per tiller of all nutrients decreased until death of the tillers during the winter. Non‐flowering tillers continued to accumulate nutrients steadily throughout the whole period of the experiment. These obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1963
1963
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…(Lemaire et al, 1985). La même approche a été réalisée pour les teneurs en P et K de graminées fourragères (Salette, 1982;Salette et al, 1982;Salette et Huché, 1989 (Williams, 1957). Dans notre situation, l'épiaison du dactyle a lieu à la première dé-cade du mois de juin (Duru et Gibon, 1989 (Callot et al, 1982;Claasen et al, 1986), du mm pour P (Callot et al, 1982).…”
unclassified
“…(Lemaire et al, 1985). La même approche a été réalisée pour les teneurs en P et K de graminées fourragères (Salette, 1982;Salette et al, 1982;Salette et Huché, 1989 (Williams, 1957). Dans notre situation, l'épiaison du dactyle a lieu à la première dé-cade du mois de juin (Duru et Gibon, 1989 (Callot et al, 1982;Claasen et al, 1986), du mm pour P (Callot et al, 1982).…”
unclassified
“…This is to be expected when consideration is given to the annual sequence of tiller production in the grass crop. Williams (16) has shown that the growth of the grass plant follows a distinct sequence. Successive groups of short-lived tillers are produced, each group tending to he larger in number, but composed of tillers of reduced size.…”
Section: Discussionmentioning
confidence: 99%
“…In plicatulum, nitrogen uptake by fertile tillers compared with vegetative tillers was reduced in Henzell & Oxenham's experiment (1964). Similarly, Williams (1957) showed that flowering tillers of timothy take up nitrogen at an increasing rate until about the time of ear emergence, when accumulation of the element ceases.…”
Section: Acs 8lmentioning
confidence: 98%